Earthquake-resistant CLT buildings stiffened with vertical steel ties. (August 2021) - Pacchioli, Stefano; Pozza, Luca; Trutalli, Davide; Polastri, Andrea
Abstract: The interest in multi-storey CLT buildings in seismic areas is leading to the development of new strategies to increase the lateral stiffness of shear walls and to resist high tensile forces due to rocking. Both these purposes can be achieved with vertical steel ties placed at each shear-wall end, to directly transfer tensile forces from each storey to the foundation. Three technologies are proposed for transferring forces from CLT panels to the ties: the use of nailed plates, of screwed connectors, or directly by contact with a thick plate at the top of each storey wall. The dynamic behaviour of CLT shear walls, representing the bracing system of a building and anchored with the aforementioned technologies, has been investigated by means of dynamic analyses and a comparison with the use of common nailed plates or screwed connections without ties. Results, varying the number of storeys and the seismic mass, show that the proposed technology is an effective strategy to increase the feasibility of multi-storey CLT buildings. Complementary non-linear static analyses have been performed to evaluate the actual displacement capacity and ductility of the systems. Highlights: An original earthquake-resistant system for multi-storey CLT buildings is presented. The system is based on the use of vertical steel ties at each shear-wall end. The steel ties transmit tensile forces directly from each storey to the foundation. The steel ties withstand high tensile forces and stiffen the structure. Forces can be transferred to ties by nailed plates, screwed connectors or contact.